IMMEDIATE EFFECTS OF INVERSE RATIO BREATHING VERSUS DIAPHRAGMATIC BREATHING ON INSPIRATORY VITAL CAPACITY AND THORACIC EXPANSION IN ADULT HEALTHY FEMALES (International Journal of Physiotherapy, 2016)
Background: The normal inspiratory to expiratory ratio is 1:2.However, the duration of inspiration can be increased voluntarily till the ratio becomes 2:1.This is called as inverse ratio breathing. The effects of inverse ratio ventilation have been studied on patients with respiratory failure and Acute Respiratory Distress Syndrome. No studies have been carried out to study the effects of inverse ratio breathing in voluntarily breathing individuals. Hence this study was carried out to find the immediate effects of inverse ratio breathing versus diaphragmatic breathing on inspiratory vital capacity and thoracic expansion.Methods: 30 healthy adult females in the age group 20-25 years were included in the study. Inspiratory vital capacity and thoracic expansion at 2nd, 4th and 6th intercostal space was measured using a digital spirometer and an inelastic inch tape respectively. Diaphragmatic breathing was administered for one minute and the same parameters were measured again. A washout period of one day was given and same outcome measures were measured before and after individuals performed inverse ratio breathing with the help of a visual feedback video for one minute.Results: Data was analysed using Wilcoxon test. There was extremely significant difference between the mean increase in the inspiratory vital capacity and thoracic expansion at the 2nd, 4th and 6th intercostals space after inverse ratio breathing as compared to diaphragmatic breathing (p < 0.0001).Conclusion: Inspiratory vital capacity and thoracic expansion increase significantly after inverse ratio breathing.